Lack of T-bet reduces monocytic interleukin-12 formation and accelerates thrombus resolution in deep vein thrombosis - Schönfelder, Tanja (Sci Rep, 2018)
The role of leukocytes in deep vein thrombosis (DVT) resolution is incompletely understood. We determined how depletion of lysozyme positive (LysM(+)) cells and a switched-off type 1 immune response influences thrombus resolution. DVT was induced in 12-week-old male mice by inferior vena cava (IVC) stenosis. Toxin mediated depletion of myeloid cells improved thrombus resolution in mice with Cre-inducible expression of the diphtheria toxin receptor in LysM(+) cells. This correlated with decreased CD45(+) cells, a population shift of Gr-1(+) to Gr-1(−) CD11b(+) myelomonocytic cells (flow cytometry) and an increase in CC-chemokine ligand 2, interleukin-4 and interleukin-10 mRNA expressions. Tbx21(−/−) mice (lacking transcription factor T-bet and marked by an attenuated type 1 immune response) with DVT had faster thrombus resolution, a reduction of pro-inflammatory Ly6C(hi) monocytes in thrombi and decreased interleukin-12p40 mRNA expression than control mice resulting in increased vascular endothelial growth factor mRNA expression and improved neovascularization of thrombotic veins. Transfer of Tbx21(−/−) bone marrow into irradiated Tbx21(+/+) recipients lead to accelerated thrombus resolution with lower T-bet-dependent interleukin-12p40 mRNA levels following IVC-stenosis. We conclude that inhibition of Tbet(+) interleukin-12 forming myelomonocytic cells accelerated thrombus resolution. Modulating the inflammatory immune response might be an approach to improve therapy of DVT.